John Hooper and his networks - Dalton, AJ (2008)
The research is a study of the context of the life and work of John Hooper, Bishop of Gloucester and Worcester, 1551-1555. It charts the nature of his relationships with friends, patrons, mentors, colleagues, and lay and clerical supporters and opponents in England and on the Continent, through the study of ecclesiastical, political, business and economic, intellectual, official and judicial, kinship and social networks in which he was involved. Its purpose is to reveal the complex mix of societal and confessional pressures influencing Hooper's approach and constraining his freedom of manoeuvre, and to a large extent determining how successful he was at achieving change. The study reveals key determinants of the nature and direction of the Reformation in England. It shows that the pressure to change doctrinal allegiances and to accommodate reformed church practices challenged not only personal confessional loyalties but also the very framework of society; that is, familial and social ties, economic, business and judicial groupings, educational affiliations, and ruling oligarchies. Within these societal networks there existed the momentum for, and resistance to, religious change. Confessional allegiances were just part of a complex mix of political and social pressures that included the exercise of patronage and protection, the use of conflict and compromise, the practise of different obligations, allegiances and loyalties, the employment of status and kinship, and the accommodation of various alliances and means of association. All of these influenced Hooper's approach and scope for action. As such, the research provides insight into why and how, in the development of the newly-reformed church in England, thoroughgoing religious change was resisted and contained.